Standar Akuntansi : Kualitas Standar dan Konsekuensi Ekonomi - Meinarni Asnawi (Jurnal Akuntansi dan Bisnis, 2007)
The article discusses quality and implications of economic consequences in standard accounting. A high quality accounting standard improves financial reporting by enhancing financial statement users’ abilities to make investment and credit decisions. Financial statement data are often used by regulatory bodies in the discharge of regulatory objectives. In such instances, changing accounting standards will have economic consequence–it will change regulatory relationships. Standard setting in the accounting fields is a political process, although many management accountants and accounting practitioners do not want to accept this conclusion (Murray and Mahaney:1986). Process of Standard accounting have four steps. First discusses the purposes served by setting accounting standard, second considering the process of regulation, third considering economic consequence and finally implementation. As a consequence, lobbying activity for accounting standard is carried on by those groups in society that have the most to gain and most to lost, i.e, large companies. Finally , economic consequence cannot be ignored when standards are set. On the other hand, conceptual, logical and technical accounting considerations are also essential to maintaining and improving existing standards. The real issue is striking a balance between the two. The fundamental reason for primacy of conceptual consideration is importance of neutrality and objectivity to a credible and effective standard setting process.